2021
DOI: 10.30621/jbachs.857712
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Factors Affecting the Length of Stay in Hospital of Transcatheter Aortic Valve Implantation (TAVI) Cases

Abstract: INTRODUCTIONAccording to the population projections made by the Ministry of Health in 1996, it is estimated that the population aged 65 and over will be 12.1% in our country in 2030 (1). In the geriatric age group, systems work in balance under physiological conditions, with reduced organ and reserve capacity. Atrophic and fibrotic changes in the aging process also affect the aortic valve. Aortic stenosis (AS) is the most common valvular heart disease in adults over 65 (2). Moderate ABSTRACT Purpose: In the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…Although there was no difference between the groups in our study, hypertension was the most common comorbidity. This result was similar to many studies [14,15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although there was no difference between the groups in our study, hypertension was the most common comorbidity. This result was similar to many studies [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…Büyükçoban et al [14] and Çakıer et al [15] reported the mean age of patients who underwent TAVI as 78.25±8.24 and 78.19±6.90, respectively. In our study, the mean age was 75.99±7.83 years and was consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%